On Agarwal–Pang-type integral inequalities - Zhao, C.J.; Bencze, M. (Український математичний журнал, 2012)
We establish some new Agarwal–Pang-type inequalities including second-order partial derivatives. In special cases, our results yield some correlated results and provide new estimates for the inequalities of this type.